ANALISIS KEGAGALAN PENANGANAN PARKIR LIAR DI KAWASAN STADION PAKANSARI KABUPATEN BOGOR - Wawan Hari Subagyo; Muhlis; Ferdian Ardiliansyah (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
This study uses a qualitative approach with data collection methods of interviews, field observations, and documentation studies. The analysis was conducted using the Fishbone Diagram method and simple weighting. The results of the study indicate that the main causes of the failure of illegal parking management include the lack of official parking spaces, weak supervision and law enforcement, suboptimal inter-agency coordination, and resistance from the community and surrounding businesses. Fishbone analysis and simple weighting analysis revealed that there are three main problems that cause the failure of illegal parking management at Pakansari Stadium. The three main causes are as follows: 1) The parking area is intended for stadium activities so it is far from busy areas with a weight of 39 with a weight of 9.8% which is included in the high category. 2) There is no collaborative policy between agencies regarding parking management with a weight of 39 with a weight of 9.8% which is included in the high category. 3) The development of technological infrastructure is not a top priority, with a weighting of 39 with a weighting of 9.8%, which is included in the high category.